Histone H2A variants play a key role at DNA double-strand breaks during repair pathway choice - Clerf, Emile; Galloy, Maxime; Fradet-Turcotte, Amélie; Côté, Jacques (Frontiers in Epigenetics and Epigenomics, 2024)
Histone post-translational modifications and variants play crucial roles in the adaptability of chromatin structure, facilitating rapid responses necessary for biological processes such as transcription, replication, and DNA damage signaling. Notably, DNA double-strand break (DSB) signaling heavily relies on these histone modifications, with signal amplification and the recruitment of specific DNA repair factors being dictated by them. Among the histones, H2Aand its variants are central to this response, with phosphorylation of the variant H2A.X being the initial and most characteristic histone mark deposit upon DNA damage detection.Additional post-translational modifications of H2A and its variants contribute to the selective recruitment of DNA repair factors and influence the choice of DNA repair pathways. This review provides a summary of current knowledge regarding the roles of histone H2A posttranslational modifications and variants in DSB signaling and repair, with a particular emphasis on modifications and variants that impact the choice of repair pathways. Additionally, the involvement of histone chaperones, chromatin modifiers, and remodelers in these processes is discussed.